Artificial Intelligence and Islamic Educational Management: A Theoretical Review for School Education - Roby Romadany; Fajar Santoso; Bhenu Arthac (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
Artificial Intelligence (AI) is reshaping educational management by augmenting decision-making, optimizing administrative processes, and enabling learner-centered ecosystems aligned with Education 4.0 paradigms. Systematic evidence from higher education shows AI integration is approaching an inflection point comparable to the internet’s arrival, with broad institutional implications for strategy, governance, and resource allocation. This study aims to analyze the relationship between artificial intelligence and educational management. A theoretical literature review is conducted and a conceptual framework for additional research is offered in order to achieve the goals and objectives of the study. In the current research, the authors consider the sales of educational management as dependent variable affected by AI. The promise of AI is inseparable from its challenges. Issues of bias, fairness, data privacy, and ethical accountability require robust governance frameworks and human oversight. Sustainable adoption depends on infrastructure modernization, capability-building, and inclusive design practices that ensure equitable access and avoid widening digital divides. AI in educational management is best understood as a dual empowerment process: it strengthens both educational outcomes and institutional performance, provided leaders invest in governance, infrastructure, and talent development.